The criminal jurisdiction and the indigenous in Colombia (2009)
From a socio-legal approach, this article sets out to analyze the material validity that the penal jurisdiction and indigenous jurisdiction law have at the moment in Colombia. In order to achieve this objective, the text describes, contextualizes and anal